Economics of Ecotourism: A Study on Orissa - Mohapatra, Nihar (Indian Journal of Marketing, 2011)
Man has finally realized the importance of natural environment. Every little step towards restoration of nature is welcomed in this environment conscious community. Every aspect of this society is taking a step ahead towards the conservation of natural resources. So how tourism will be left out? Ecotourism is one of the outcomes of this consciousness. Ecotourism is "Responsible travel to natural areas that conserves the environment and improves the well-being of local people". Though Orissa government has taken steps to improve tourist spots to generate more revenue, but mother Orissa is still full of other beautiful scenic places which are yet to be explored. This paper has analyzed the change in tourism industry in years and has tried to give few suggestions for further improvement. The researcher has also highlighted some major ecotourism spots of Orissa. Tourism can become Orissa’s core competency sector creating employment, enhancing production, productivity and contributing significantly towards development of the state.